Glaucomatous Visual Field Defect Severity and the Prevalence of Motor Vehicle Collisions in Japanese: A Hospital/Clinic-Based Cross-Sectional Study - Takeshi Ono; Kenya Yuki; Ryo Asaoka; Keisuke Kouyama; Takayuki Abe; Sachiko Tanabe; Kazumi Fukagawa; Miki Uchino; Masaru Shimoyama; Yoko Ozawa; Naoki Ozeki; Daisuke Shiba; et al. (Journal of Ophthalmology)
Purpose. This study examined the association between the severity of visual field defects and the prevalence of motor vehicle collisions (MVCs) in subjects with primary open-angle glaucoma (POAG). Methods. This is a cross-sectional study. Japanese patients who have had driver’s licence between 40 and 85 years of age were screened for eligibility. Participants answered a questionnaire about MVCs experienced during the previous 5 years. Subjects with POAG were classified as having mild, moderate, or severe visual field defect. We evaluated associations between the severity of POAG and the prevalence of MVCs by logistic regression models. Results. The prevalence of MVCs was significantly associated with the severity of POAG categorized by worse eye MD (control: 30/187 = 16.0%; mild POAG: 17/92 = 18.5%; moderate POAG: 14/60 = 23.3%; severe POAG: 14/47 = 29.8%; P=0.025, Cochran-Armitage trend test). Compared to the control group, the adjusted OR for MVC prevalence in subjects with mild, moderate, or severe POAG in the worse eye was 1.07 (95% CI: 0.55 to 2.10), 1.44 (95% CI: 0.68 to 3.08), and 2.28 (95% CI: 1.07 to 4.88). Conclusions. There is a significant association between the severity of glaucoma in the worse eye MD and the prevalence of MVCs.